Nickel-Catalyzed Cross-Electrophile [2+4] Annulation of Benzynes - Dong, Haiyan; Ding, Xinrang; Wang, Chuan (Synlett, 2025)
Cross-electrophile coupling (XEC) reactions have emerged as powerful tools for C–C bond formation, whereas annulation employing arynes provides unique approaches to polycyclic arenes. Herein, we report a nickel-catalyzed cross-electrophile [2+4] annulation using benzynes and a 1-bromo-2-(2-chlorovinyl)arenes as C-2 and C-4 synthons, respectively. This proof-of-concept study not only provides a new method for synthesizing polysubstituted phenanthrenes, but also substantiates the feasibility of merging XEC reaction and aryne chemistry.
Keywords: benzynes; [2+4] annulation; nickel catalysis; phenanthrenes; reductive cross-coupling; cross-electrophile coupling